A Preliminary Report on Pelvic Floor Reconstruction through Colpocleisis from 2001 to 2007 at the University Hospital of the Puerto Rico Medical Center - Marrero, Camil; Aponte, Anamar; Torres, Rosimar; Santos, Fidel; Rivera, Juana (Puerto Rico Health Sciences Journal, 2010)
Objective: Describe the pre-, intra-, and postoperative experience of colpocleisis in a group of patients at the University Hospital of the Puerto Rico Medical Center. Methods: A chart review was done on a subgroup of patients, 70 years or older, on which colpocleisis was performed between January 2001 and December 2007. The evaluation included demographics, comorbidities, and previous pelvic surgeries. The Pelvic Organ Prolapse Quantification (POP-Q) System was used to evaluate pelvic organ prolapse. Surgical procedures, outcomes, and related data were tabulated. Results: Nineteen patients with a mean age of 77 years underwent the procedure, 57.8% presenting more than one comorbidity. Seventy-three percent of the patients had a BMI over 25. Sixty-three percent reported prior pelvic surgeries, 94.7% had stage IV pelvic prolapse, and 73.6% underwent concomitant procedures. Spinal anesthesia was most often used (68%), and the mean hospital stay was 2.1 days. Thirty-one percent of interviewed patients reported preoperative impairment in their daily activities that resolved completely after surgery. Incontinence symptoms resolved in 69% of patients. Ninety-two percent of the patients reported full satisfaction with the surgery. Conclusion: Colpocleisis is a safe pelvic reconstructive procedure for high-risk patients with multiple comorbidities. Regional anesthesia can be offered with minimal blood loss, short operative time, and early ambulation.